KUALITAS PELAYANAN PUBLIK DI KANTOR KECAMATAN NEGLASARI KOTA TANGERANG - Nugraha, Andhika; Hardian, Dafyar Eliadi; Mulyadi, Edi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze the quality of public services at the Neglasari District Office in Tangerang City, focusing on the effectiveness, efficiency, responsiveness, and accountability of the bureaucracy. The background to this research is based on persistent public complaints regarding administrative services, which are perceived as slow, non-transparent, and suboptimal in the use of information technology. The research method used is a descriptive qualitative approach, with data collection techniques through in-depth interviews, observation, and documentation studies. The research informants consisted of district officials and the public as service users. The results indicate that the quality of public services in Neglasari District has improved in terms of information transparency and apparatus discipline, but challenges remain in terms of service speed, consistency of standard procedures, and limited infrastructure. The analysis uses the service quality theory according to Zeithaml, Parasuraman, and Berry (SERVQUAL), which encompasses the dimensions of tangible, reliability, responsiveness, assurance, and empathy, indicating that responsiveness and tangible are the weakest dimensions. Furthermore, Albert S. Humbyres's theory of public service emphasizes the importance of humanistic, adaptive, and community-satisfaction-oriented services. In the context of this research, this approach still requires strengthening, particularly in terms of communication and community assistance. The study concludes that improving the quality of public services at the Neglasari District Office requires strengthening the capacity of civil servants, optimizing the use of digital technology, and consistently improving minimum service standards. Research recommendations focus on developing a service system strategy based on transparency, public participation, and improving human resource competency. Keywords: Public Service Quality, Responsiveness, Albert S. Humbyres' Theory.